Students’ literature achievement: Predictors investigation research - Alita Arifiana Anisa (REID (Research and Evaluation in Education), 2017)
This research is an expost facto research which aims to find out the exsistence of the mean difference between gender in terms of achievement, and investigate the variables predicting students’ achievement in literature study including the direct/indirect effect. This research involved 90 students established ramdomly as the sample. The research used the quantitative data analysis to analyze the mean difference between groups and the direct/indirect effect of the predictors. The result of this research shows that: (1) girls have higher achievement in literature study compared to boys; (2) the predictors that are statistically proven as a direct significant predictor of students’ final test score are gender, second dummy variable for class and mid-term test, while the rest of predictors (except the first dummy variable of class) contribute indirectly to the prediction of students’ achievement in literature study; and (3) the magnitude of the predictors might be different when they are applied in different classes.